The Dark Side of Personality: Anti-Sociality Increases Strategic Game Play - Jan Engelmann; Basil Schmid; Justin Chumbley; Ernst Fehr (Tinbergen Institute, 2018)
We assess the role of anti-social personality traits in explaining heterogeneity in commonly observed social preferences. We identified a personality profile that clearly reflects anti-social personality characteristics, with high positive loadings on Machiavellianism and high negative loadings on empathy, trustworthiness and agreeableness. Anti-sociality predicts decision strategies in a manner that is consistent with its name: significantly lower levels of trust and decreased trustworthiness. To identify the strategic nature of anti-social behavior in changing environments, we assessed the moderating role of personality on investor trust and trustee reciprocity in the presence relative to the absence of the investor's option to punish. Our results show that only the anti-social personality profile is associated with specific payoff maximizing strategy shifts induced by these environmental changes: when punishment was not available to investors, we observe significantly lower levels of investor trust and trustee reciprocity, while there is a significant increase in both behaviors when punishment was available. These effects were specific for anti-sociality, as no other personality factor was associated with such a strong adjustment of decision strategies in the presence of punishment. These results demonstrate that anti-social personality characteristics are associated with strategic behavioral shifts aimed at maximizing the extraction of resources from their counterparts. The reliability of the strategic effects of anti-social personality during trust, reciprocity and punishment strongly supports the notion that self-projection underlies anti-social decision-making.
Keywords: C71; D87; D91; 330; trust; reciprocity; punishment; anti-social; personality; individual differences